Manajemen Kinerja di Institusi Pendidikan Tinggi: Kepuasan Kerja dan Budaya Organisasi - Siti Nur Hidayah (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2016)
Individual performance in the organization is influenced by many factors, such as work satisfaction and culture within the organization. Besides that, work satisfaction have a positif correlation with individual performance. The more satisfy a worker with his/her work, the bettter his/her individual performance that make them to be more productive. Organizational culture influence which strategy that will be implemented by an organization to respond to the changes within or outside the organization. The more capability of an organization to respond to changes, the better the organization itself.